On the principles of compatibility of cognitive and evolutionary and possibilist approaches in studying tendencies of lose and gain of transition by Russian verbs - Некрылова, Ольга Леонидовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article argues that studying tendencies of lose and gain of transition by Russian verbs has to be grounded on methodological base representing unification of cognitive and evolutionary and possibilist approaches. The cognitive and linguistic preconditions of such unification have been shown, i.e. principles of explanation and interdisciplinary. The essence of cognitive and evolutionary approach as the methodology of evolutionary epistemology has been discovered. The possibilist approach elaborated on the basis of philosophy of possibility created by M. H. Epshtein has been presented. Possibility of unification of cognitive and evolutionary and possibilist approaches for studying tendencies of lose and gain by Russian verbs of transition has been demonstrated and examples of united interpretations of such tendencies have been shown.